2006
DOI: 10.1152/ajplung.00053.2006
|View full text |Cite
|
Sign up to set email alerts
|

Role of substance P in hydrogen sulfide-induced pulmonary inflammation in mice

Abstract: We have shown earlier that H(2)S acts as a mediator of inflammation. In this study, we have investigated the involvement of substance P and neurogenic inflammation in H(2)S-induced lung inflammation. Intraperitoneal administration of NaHS (1-10 mg/kg), an H(2)S donor, to mice caused a significant increase in circulating levels of substance P in a dose-dependent manner. H(2)S alone could also cause lung inflammation, as evidenced by a significant increase in lung myeloperoxidase activity and histological eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 25 publications
3
81
1
Order By: Relevance
“…Activation of TRPV1 thereby results in an influx of Ca 2ϩ and induces depolarization of nerves and SP release from nerve terminals (36). Similarly, our previous study has also shown that ablation of sensory nerves with capsaicin or pretreatment with capsazepine, a TRPV1 antagonist, protected mice from H 2 S-induced lung inflammation (25). In light of the data obtained from the present study and earlier studies, we propose that under different conditions, H 2 S may regulate the release or production of SP by different pathways, including up-regulating the PPT-A gene and stimulating TRPV1.…”
Section: Figurementioning
confidence: 65%
See 3 more Smart Citations
“…Activation of TRPV1 thereby results in an influx of Ca 2ϩ and induces depolarization of nerves and SP release from nerve terminals (36). Similarly, our previous study has also shown that ablation of sensory nerves with capsaicin or pretreatment with capsazepine, a TRPV1 antagonist, protected mice from H 2 S-induced lung inflammation (25). In light of the data obtained from the present study and earlier studies, we propose that under different conditions, H 2 S may regulate the release or production of SP by different pathways, including up-regulating the PPT-A gene and stimulating TRPV1.…”
Section: Figurementioning
confidence: 65%
“…We have previously reported that i.p. administration of NaHS in normal mice caused a significant rise in the circulatory level of SP in a dose-dependent manner, coupled with obvious lung inflammation (25). Similarly, in rat bladder, H 2 S at a physiological concentration was capable of stimulating capsaicin-sensitive primary afferent neurons with a consequent release of tachykinin, in turn leading to the contractile response of the smooth muscles (22,23).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Similarly, pretreatment of rats with PAG for 1 h prior to blood withdrawal was also protective as PAG increased heart rate recovery time, significantly reduced liver, lung and plasma levels of TNF-a and IL-6 and, in the liver, PAG reduced neutrophilic accumulation and tissue damage [35]. Conversely, administration of H 2 S donors based on sulfide salts (see later), such as sodium hydrosulfide (NaSH) to animals either alone or in combination with LPS, induce marked hypotension, liver, lung and kidney inflammation and aggravated multiple organ injury through upregulation of tissue NF-kB, p38 and ERK1/2 signaling [36][37][38].…”
Section: H 2 S and Acute Whole-body Inflammation (Sepsis)mentioning
confidence: 99%